Development Fundamental Movement Learning Model Based On Team Games Tournament (TGT) For Elementary School Children - Fahrudin Fahrudin; Moch Asmawi; Firmansyah Dlis; Resty Gustiawati (UNIB Press, 2020)
This study aims to develop a fundamental basic motion model based on the Team Games Tournament (TGT) for elementary school children. This study uses a research approach development of Research and Development (R&D) research and development model Borg and Gall. Development of a fundamental Motion Learning Model that will be developed in accordance with the characteristics of children aged 6-12 years who are at the elementary school level.The data collection technique starts from the analysis of the need for the development of fundamental basic movements, the making of initial product drafts, expert validation, product improvement, small-scale trials, first revisions, field trials, second revisions, final fundamental basic motion learning model product results. The research sample in the needs analysis of 10 respondents (teachers of Physical Education, Sports and Health) with the generalization results that70% of respondents said they needed the development of a TGT-based fundamental motion learning model and were willing to use basic motion development models to improve children's fundamental basic movement mastery. Then testing the development of the fundamental-based motion learning model Team Games Tournament (TGT)in the small-scale trial, there were 30 students at SDN Kalangsurya III, Rengasdengklok District and 10 students in the main field test at SDIT Salman Al-Farisy and SDN Kalangsari III, Rengasdengklok District. All forms of obstacles in the trial of the development of the TGT-based fundamental motion learning model and practitioners' input have been revised for the sake of product development perfection. Thus the development of a fundamental based motion learning model Team Games Tournament (TGT) for elementary school children it is declared fit for use in the learning process of Physical Education, Sports and Health in primary schools in accordance with the material in related basic competencies.